2005
DOI: 10.1097/01.opx.0000192349.11525.de
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flat and Steep Rigid Contact Lens Fitting Methods in Keratoconus

Abstract: The data reported here indicate that, after controlling for disease severity in the form of corneal curvature, keratoconic eyes fitted with a rigid contact lens resulting in an apical touch fluorescein pattern did not have an increased risk of being scarred centrally at baseline. This "natural history" sample cannot determine causal proof that one method of fitting lenses is safer than another. To achieve this, a randomized clinical trial is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 15 publications
1
29
0
5
Order By: Relevance
“…Steeper corneal curvature increased the risk of prevalent corneal scarring by 28% per diopter of increased curvature (adjusted OR, 1.28; 95% CI, 1.23-1.34; p = 0.0001). [21] Visual acuity and corneal curvature had the strongest association with vision-related quality of life. [22] Binocular, entrance visual acuity worse than 20/40 was associated with lower quality of life scores on all scales except General Health and Ocular Pain.…”
Section: Baseline Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Steeper corneal curvature increased the risk of prevalent corneal scarring by 28% per diopter of increased curvature (adjusted OR, 1.28; 95% CI, 1.23-1.34; p = 0.0001). [21] Visual acuity and corneal curvature had the strongest association with vision-related quality of life. [22] Binocular, entrance visual acuity worse than 20/40 was associated with lower quality of life scores on all scales except General Health and Ocular Pain.…”
Section: Baseline Findingsmentioning
confidence: 99%
“…Controlling for disease severity (corneal curvature assessed by FDACL), the risk of corneal scarring did not increase with flat versus steep rigid contact lens fit (adjusted OR, 1.83; 95% CI, 0.79-4.23; p = 0.16). [21] Steeper corneal curvature increased the risk of corneal scarring by 26% per diopter of increased curvature (adjusted OR, 1.26; 95% CI, 1.17-1.35; p< 0.0001).…”
Section: Longitudinal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Edrington et al 23 found that 88% of 1209 CLEK patients were fitted with flat-fitting lenses compared with 12% of patients who wore steep-fitting lenses; similar findings have been noted in other reports also. 6,12,26 Edrington et al 23 discovered that the CLEK group's severe keratoconic patients wore the flattest fitting lenses when compared with moderate and mild keratoconic patients. A possible reason for this popularity of flatter-fitting lenses is that they can offer comparatively better visual acuity than steeper-fitting lenses.…”
mentioning
confidence: 98%
“…6 In normal subjects, corneal curvature changes observed following RGP contact lens wear are related to the type of contact lens worn and the number of years of lens wear. 5 It has been reported that apical-touch fitting causes central corneal flattening in keratoconus, 7 whereas apicalclearance fitting causes central corneal steepening, 8 which could be confounded with the normal progression of keratoconus disease, so apical-clearance fitting approach is not normally used. Zadnik and Mutti 9 previously discussed that apical-touch fitting of RGP lenses might 'mold' the keratoconic cornea by exerting pressure on the cone apex, thereby forcing the anterior surface to conform with the RGP lens' back surface.…”
Section: Introductionmentioning
confidence: 99%